Our Applications of The Paramedian Forehead Flap in The Reconstruction of Nasal Defects - Bulut, Fatih; Demir, Canser Yılmaz (Fırat University, 2003)
Aim: Massive defects of the nose resulting from excision of tumoral masses may not be amenable to reconstruction using skin grafts. Therefore, in this study we evaluated our results of paramedian forehead flap in the reconstruction of nasal defects. Materials and method: Paramedian forehead flap was employed in 10 patients (7 men, 3 women; mean age 63,2 ±10,4 years; range 44 to 82 years) with major nasal defects between June 2000 and March 2003 in our clinic. There were tissue defects in all cases due to surgical resection of tumoral masses. Results: The reconstruction with paramedian forehead flap revealed out satisfactory results in all cases. There were no problems to be concerned with the flap and donor site. Conclusion: The paramedian forehead flap allows the transfer of forehead tissue in an efficient and reliable manner with minimal deformity and creates the aesthetically pleasing reconstruction.

Amaç: Tümöral kitlelerin eksizyonu sonrasında oluşan burun defektlerinin rekonstrüksiyonunda cilt greftlerinin kullanımı yeterli olmayabilir. Bu amaçla; çalışmamızda burun defektlerinin rekonstrüksiyonunda paramedian alın flebi kullandık ve sonuçlarımızı değerlendirdik. Gereç ve yöntem: Haziran 2000 ve Mart 2003 tarihleri arasında kliniğimizde majör burun defekti bulunan 10 olgunun (7 erkek, 3 kadın; ortalama yaş 63,2±10,4 yıl; dağılım 44-82 yıl) rekonstrüksiyonu paramedian alın flebi ile gerçekleştirildi. Olguların tümünde tümör cerrahisine bağlı doku kaybı mevcuttu. Bulgular: Bütün olgularda paramedian alın flebi ile rekonstrüksiyon tatmin edici sonuçlar vermiştir. Flep ve donör saha ile ilgili olarak hiçbir problem yaşanmadı. Sonuç: Paramedian alın flebi alından yeterli miktarda doku transferini güvenilir bir şekilde mümkün kılarak, çok az deformite ile estetik açıdan memnun edici bir rekonstrüksiyon sağlar.
Burun Defektlerinin Onarımında Paramedian Alın Flebi